2022
DOI: 10.5847/wjem.j.1920-8642.2022.068
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils inhibit CD8+T cells immune response by arginase-1 signaling in patients with sepsis

Abstract: BACKGROUND: Patients with sepsis often exhibit an acute inflammatory response, followed by an immunosuppressive phase with a poor immune response. However, the underlying mechanisms have not been fully elucidated. METHODS:We sought to comprehensively characterize the transcriptional changes in neutrophils of patients with sepsis by transcriptome sequencing. Additionally, we conducted a series of experiments, including real-time quantitative polymerase chain reaction (RT-qPCR) and flow cytometry to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Indeed, the predictive value of these components may be linked to the complicated mechanisms underlying the contribution of NETs to postresuscitative vital organ damage (especially brain damage) (9,15,23). Neutrophils are the most abundant type of white blood cells in circulation and constitute the front line of host immune defense, which is closely associated with the diagnosis and outcomes of inflammation-related diseases (31)(32)(33)(34)(35)(36)(37). In addition to the classical defense mechanisms of neutrophils, such as phagocytosis, ROS production, and degranulation, the NETs formed by these cells play a vital role in host immune defense (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the predictive value of these components may be linked to the complicated mechanisms underlying the contribution of NETs to postresuscitative vital organ damage (especially brain damage) (9,15,23). Neutrophils are the most abundant type of white blood cells in circulation and constitute the front line of host immune defense, which is closely associated with the diagnosis and outcomes of inflammation-related diseases (31)(32)(33)(34)(35)(36)(37). In addition to the classical defense mechanisms of neutrophils, such as phagocytosis, ROS production, and degranulation, the NETs formed by these cells play a vital role in host immune defense (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are key players in inflammatory cell infiltration in different cancer types and can inhibit CD8 + T cells in the antitumor immune response. 30 CD11b is involved in immunity regulation by inducing neutrophil differentiation. 31 In this study, we found that COLEC12 was significantly correlated with CD11b in GC, suggesting that COLEC12 may inhibit tumor immunity by mediating neutrophils and their correlation with CD11b.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs and macrophages may contribute to the suppression of immunity in patients with CHB through the production of immunomodulatory cytokines such as interleukin (IL-10) and tumor growth factor (TGF-1) (Wang et al ., 2022) .Furthermore, it has been shown through studies that myeloid-derived suppressor cells (MDSC) in the liver microenvironment have the ability to suppress T-cell signalling in part through hydrolyze arginine and significantly inhibit the T-cell effect or function (Dai et al, 2022).…”
Section: Hepatitis Viruses Immune Responses 1 Hepatitis B Immune Resp...mentioning
confidence: 99%